Effectiveness of fitness and nutritional status on learning outcomes in students penjas fkip islamic university of riau - Zulrafli Zulrafli; Ricky Fernando Fernando; Oki Candra (Journal Of Sport Education (JOPE), 2023)
(English)This study aims to investigate the relationship between physical fitness and nutritional status and the learning outcomes of physical education students at FKIP Riau Islamic University. The research method used is a quantitative descriptive study. The sample population is class 5A and 5B physical education (penjas) students at FKIP Riau Islamic University. Purposive sampling technique. The physical fitness measurement test uses the 2.4 km Cooper test and the nutritional status test uses height, weight and body mass index, while learning achievement uses the cumulative achievement index. The data analysis technique uses multiple analysis techniques using SPSS 22. The research results show that the effectiveness of physical fitness and nutritional status on student learning achievement is 24.10%. These findings have important implications in the educational context, especially in physical education study programs. Encouraging students to maintain optimal physical fitness and nutritional status can improve learning outcomes. Therefore, it is recommended that educational institutions consider integrating physical fitness and nutrition education programs in the curriculum to improve student academic performance. (Indonesian)Penelitian ini bertujuan untuk menginvestigasi hubungan antara kebugaran fisik dan status gizi dengan hasil belajar mahasiswa pendidikan jasmani FKIP Universitas Islam Riau. Metode penelitian yang digunakan adalah studi deskriptif kuantitatif. Populasi sampel yakni kelas 5A dan 5B mahasiswa pendidikan jasmani (penjas) FKIP Universitas Islam Riau. Teknik penarikan sampel purposive sampling.  Tes pengukuran kebugaran fisik menggunakan Cooper tes 2,4 km dan tes status gizi digunakan melalui tinggi badan, berat badan dan di cari indek masa tubuh sedangkan prestasi belajar melalui indek prestasi komulatif. Teknik analisis data menggunakan teknik analisis berganda dengan menggunakan SPSS 22. Hasil penelitian terdapat efektifitas kebugaran fisik dan status gizi terhadap prestasi belajar mahasiswa sebesar 24.10%. Penemuan ini memiliki implikasi penting dalam konteks pendidikan, khususnya dalam program studi pendidikan jasmani. Mendorong mahasiswa untuk menjaga kebugaran fisik dan status gizi yang optimal dapat meningkatkan hasil belajar. Oleh karena itu, disarankan agar institusi pendidikan mempertimbangkan integrasi program kebugaran fisik dan pendidikan gizi dalam kurikulum untuk meningkatkan prestasi akademik mahasiswa.Copyright © The Author (s) 2023Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.